Preliminary In vitro Investigation of Antioxidant Potential of Ultra Short Acting Arylcarbamoyloxy-aminopropanols Containing N-Phenylpiperazine Moiety (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Abstract not availableDhaka Univ. J. Pharm. Sci. 15(2): 235-239, 2016 (December)